1964
DOI: 10.1104/pp.39.4.630
|View full text |Cite
|
Sign up to set email alerts
|

Organic Acids in the Ripening Banana Fruit

Abstract: The nonvolatile orgainic acicls uncloubte(dly play a role in fruit ripening as they (1o in many other metabolic processes. As an approach to definiing this role in the banania fruit, informatioin is needled on the nature of these acids and on the chainges which occur dluring ripening.Earlier reports (23)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1
1

Year Published

1966
1966
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 19 publications
1
19
1
1
Order By: Relevance
“…Although the latter is dominant in green fruit (Wyman & Palmer, 1964) only the first two were considered in this study since they were identified as the most important acids in the fruits starting from colour stage 4 (more yellow than green). L-malic acid contributes more to the sourness taste sensation than citric acid since it is appreciated as more tart and has a lower threshold value for human acidity perception (Stevens, Kader, Albright-Holton, & Algazi, 1977).…”
Section: Identification Of Taste Components In Banana Fruitmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the latter is dominant in green fruit (Wyman & Palmer, 1964) only the first two were considered in this study since they were identified as the most important acids in the fruits starting from colour stage 4 (more yellow than green). L-malic acid contributes more to the sourness taste sensation than citric acid since it is appreciated as more tart and has a lower threshold value for human acidity perception (Stevens, Kader, Albright-Holton, & Algazi, 1977).…”
Section: Identification Of Taste Components In Banana Fruitmentioning
confidence: 99%
“…In banana the most important taste components affecting sweetness are D-glucose, D-fructose, and sucrose (Kyamuhangire, Myhre, Sorensen, & Pehrson, 2002). For sourness, L-malic acid and citric acid (Kyamuhangire et al, 2002) are the most important taste components although some authors also report the presence of minor amounts of oxalic acid (Wyman & Palmer, 1964) and succinic acid (Kyamuhangire et al, 2002). Methods based on High-Pressure Liquid Chromatography (HPLC) are commonly used for the quantification of these components (Rudnitskaya et al, 2006;Torija et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Hulme, Jones, and Wooltorton 1965;Lance et al 1965), and of changes in metabolites (e.g. Rowan, Pratt, and Robertson 1958;Barker and Solomos 1962;Wyman and Palmer 1964), the elucidation of the key events must come from metabolic studies of organized tissues (Beevers 1961). To overcome the problems inherent in working with intact fruits, ripening at the tissue level has been studied with thin (0•5-1• 0 mm thick) disks of tissue cut from the fruit at the appropriate stages of ripening (Baur and Workman 1964;Ben-Yehoshua 1964;Richmond and Biale 1966;Sacher 1966).…”
Section: Introductionmentioning
confidence: 99%
“…The requirement to deplete oxalate from the biosphere has resulted in the evolution of several distinct mechanisms for oxalate catabolism (6,7,9,14,15,18). Two general mechanisms are decarboxylation to yield formic acid and CO2 [as in the reaction (COOH)2 -> HCOOH + CO2] and oxidation to yield hydrogen peroxide and CO2 [as in the reaction (COOH)2 + 02-> 2CO2 + H202].…”
mentioning
confidence: 99%